OBSERVASI AWAL DALAM PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK SMAN 12 PADANG - Rurisman Rurisman; Azwar Ananda; Mukhaiyar Mukhaiyar; Arnellis Arnellis (Jurnal Education and Development, 2023)
Good learning tools will make students have good mathematical reasoning abilities. This type of research is a qualitative descriptive research. Preliminary observations aimed to find, review and explain (1) the mathematical reasoning abilities of students at SMAN (2) the conditions and forms of learning tools used and developed by teachers (3) as a basic consideration in continuing research on the development of learning tools based on contextual approaches in improve students' mathematical reasoning abilities. The results of observations made at SMAN 12 Padang, it was found that the learning tools used were not maximally related to contextual matters, so that the learning that students went through was less meaningful. The learning tools used are still somewhat general and less able to improve students' mathematical reasoning abilities. An approach that can accommodate learning tools so that related learning is more meaningful is the contextual approach. Based on this, follow-up is needed in the form of research on the development of contextual-based learning tools to improve the mathematical reasoning abilities of high school students.